2022
DOI: 10.1055/a-1863-1862
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of MOG and AQP4 Antibodies and Outcomes in an Indian Cohort of Pediatric Acquired Demyelinating Syndromes

Abstract: This study aimed to determine the seropositivity of myelin oligodendrocyte glycoprotein antibodies (MOG-Ab) and aquaporin-4 antibodies (AQP4-Ab) and outcomes in children with acquired demyelinating syndromes (ADS). Children (6months-15years) with suspected ADS were enrolled and tested for MOG-Ab and AQP4-Ab prospectively over 18 months at a tertiary-care hospital in North India. Children with proven non-immune mediated neurological disorders were enrolled as controls. Of 79 children with suspected ADS, 66 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 28 publications
1
4
2
Order By: Relevance
“…10 But other studies have reported optic neuritis to be common. 16,24,31 We observed female predominance as noted earlier. 12,17,23 However, EU consortium reported equal gender distribution in MOGAD with a slight female preponderance in older children.…”
Section: Mogadsupporting
confidence: 82%
See 4 more Smart Citations
“…10 But other studies have reported optic neuritis to be common. 16,24,31 We observed female predominance as noted earlier. 12,17,23 However, EU consortium reported equal gender distribution in MOGAD with a slight female preponderance in older children.…”
Section: Mogadsupporting
confidence: 82%
“…We found MOG-IgG seropositivity of 62% which is comparable to paediatric cohorts 3,10,23 but higher compared to a study by Sankhyan et al from North India. 16 Most of the children with NMOSD had seronegative/unknown status for AQP4 IgG but neuroimaging features helped in the diagnosis. However, most of these children were diagnosed before testing for serum MOG antibodies became available hence, we cannot rule out the possibility of few of these being MOGAD.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations